Making sense of the dollar exposing dangerous myths about trade and foreign exchange - Chandler, Marc 1961- (New York Bloomberg Press, 2009)
"Making Sense of the Dollar explores the many factors--trade deficits, the dollar's role in the world, globalization, capitalism, and more--that affect the dollar and the U.S. economy and lead to the inescapable conclusion that both are much stronger than many people suppose"--Provided by publisher.
Myth 1: the trade deficit reflects U.s. competitiveness -- Myth 2: the current account deficit drives the dollar -- Myth 3: you can't have too much money -- Myth 4: labor market flexibility is the key to U.S. economic prowess -- Myth 5: there is one type of capitalism -- Myth 6: the dollar's privileged place in the world is lost -- Myth 7: globalization destroyed American industry -- Myth 8: u.s. capitalist development prevents socialism -- Myth 9: the weak u.s. dollar boosts exports and drives stock markets -- Myth 10: the foreign exchange market is strange and speculative -- Summary and some thoughts on the way forward.
Gift from Dr. William Edward James (1951-2010).
Keywords: Foreign exchange -- United States; Dollar, American; Balance of trade -- United States